The sky lords : a novel - Brosnan, John (London : Victor Gollancz, 1988)
Centuries in the future, after the world has been devastated by the Gene Wars, the scattered remnants of humanity have to struggle against both the spreading biological blight on the ground and the great airships that dominate the skies. Controlled by feudal warlords these mile-long dirigibles patrol their territories, exacting tribute from the ground communities. Any resistance to the Sky Lords results in ruthless aerial bombardment: a fate that befalls Minerva, a town which is all that remains of a former feminist state. One of the few survivors, Jan Dorvin, is taken aboard the airship Lord Pangloth. Her original intention to destroy the Sky Lord goes spectacularly awry, and she finds herself a fugitive, first in the complex society of the airship, and later in the biological nightmare of the blight lands.
part I. Lord Pangloth -- part II. The perfumed breeze.
Library's copy signed by the author.
Keywords: Airships -- Fiction; Social conflict -- Fiction; Science fiction, Australian; Australian